2015
DOI: 10.17743/jaes.2015.0074
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Based Analysis of the Effects of Packet Delay on Networked Musical Interactions

Abstract: Networked Music Performance (NMP) is a mediated interactional modality with a tremendous potential impact on professional and amateur musicians, as it enables real-time interaction from remote locations. One of the known limiting factors of distributed networked performances is the impact of the unavoidable packet delay and jitter introduced by IP networks, which make it difficult to keep a stable tempo during the performance. This paper investigates the tolerance of remotely interacting musicians towards adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…e resulting latency level represents a factor that dramatically affects the NMP experience. It has been shown that latency values in the range of 20-60 ms degrade the quality of the performance, by causing progressive slowdowns in the performance [19]. e effect of unnatural latencies has been explained in terms of incongruent temporal separation between action and auditory information, with respect to the expected "natural" time delays occurring in co-located performances [16,17,34].…”
Section: Temporal and Spatial Factors In Nmpmentioning
confidence: 99%
See 4 more Smart Citations
“…e resulting latency level represents a factor that dramatically affects the NMP experience. It has been shown that latency values in the range of 20-60 ms degrade the quality of the performance, by causing progressive slowdowns in the performance [19]. e effect of unnatural latencies has been explained in terms of incongruent temporal separation between action and auditory information, with respect to the expected "natural" time delays occurring in co-located performances [16,17,34].…”
Section: Temporal and Spatial Factors In Nmpmentioning
confidence: 99%
“…e concert is the con guration commonly investigated in NMP research and technological development [4,5,59]. Multimodal signal acquisition includes the audio recordings from both the remote environments, to compute several measures on the quality of the performance [19], gaze tracing and eye tracking to annotate the visual search of the musicians [60], and the biometric response of the performers for distress estimation [61].…”
Section: E Framework Conceptualized As Shown Inmentioning
confidence: 99%
See 3 more Smart Citations